(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The WHO considers work-related stress to be the new pandemic in the 21st century. The educational system had a great impact from 2020 onwards due to the pandemic caused by covid-19, work demands increased and with it stress. Currently, constant changes, interpersonal relationships, parental demands and adaptation to technology continue to be factors that cause stress in teachers. The study was carried out in the "18 de Octubre" Educational Unit located in the city of Quevedo. The main objective is to determine the impact of work stress on the behavior of teachers of the Educational Unit. The study was conducted under a descriptive observational type of research, measuring the variables through data collection. The population consisted of a total of 21 teachers; as an instrument, surveys with closed but relevant questions were applied to obtain information. The results show that there is emotional exhaustion and work fatigue on the part of the teachers.